An anthropometry survey of female young adults in Malaysia. - Mohd Salleh, Naimah; Othman, Mumtazah; Badari, Zainal; Azahari, Shamsul; Bohari, Sharizal (2008)
Anthropometric data and sizing systems is an important component of apparel quality. Apparel cannot be top quality unless it fits the potential wearers satisfactorily. The purpose of this research is to examine anthropometric data and to developed clothing sizing system for females young adults in Malaysia. The survey sample included 430 female students studying at University Putra Malaysia. Standard Anthropometric technique and tools were used to take body measurement. Twenty one body measurements were taken on each subject. Descriptive statistics were used as a basis to developed a standard body measurement. By using this standard, sizing system for females young adults were created. Pearson correlation was used to determine the relationship among body measurements. Results of the study showed that sample consisted of female students with an average age of 21.4 years old. The average of the key dimensions chosen (body height, bust circumference, hips circumference are 156.3cm, 82.5cm, 91.9cm respectively. The standard deviations are 5.6cm, 6.7cm, 6.8cm and their ranges are 141.2-175cm, 68-117cm, and 66-119.5cm respectively. Correlation matrix for body measurements, showed that the body length and height measurement were significantly related however there was a weak relationship between weight and body length. The lower body circumference was related mostly with leg measurement (such as thigh and ankle circumference) and upper body circumference with arm measurements (such as bicep and bicep and wrist circumference ), while weight alone is highly correlated with all the measurements. Standard deviations were used to develop sizing systems- SMALL, MEDIUM, LARGE and XTRA LARGE- which fit young female. Data from this study have the potential to provide new insights into apparel and fitting. The Malaysian apparel industry has not had access to reliable, representative anthropometric data. So tools and methodologies to harness, apply, and interprets this information are critically needed.